KEMAMPUAN BERKOMUNIKASI SISWA MELALUI PENERAPAN STRATEGI PEMBELAJARAN BERBASIS PROYEK DI KELAS XI SMA BABUSSALAM PEKANBARU - Maya Dwika Putri Dwika Putri; Yennita '; Muhammad Nor Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research is to determine the level of communication skills of students in class XI MIA 1 Babussalam Pekanbaru through the implementation of project-based learning strategy in The Equation of Progressive Wave and Stationary Wave subject. The expected benefits of this research is as a basis for further examine the success rate of students by using a lot of other learning approaches. This research was conducted at SMA Babussalam Pekanbaru precisely in March to June 2015 in class XI MIA 1 totaling 29 students. The design of the research is pre-experimental design form one shot case study. From the research, the results were obtained for oral communication skills based on indicators that include the ability of express information and ideas; paying attention when someone else speaks; responds; and asking, students have the ability with high category. Similarly to written communication skills, the ability of students in each meeting continue to increase by an average of each indicator that includes the quality of the writing and the visual representation categorized as high. So it can be concluded that communication skills of students in class XI MIA 1 SMA Babussalam Pekanbaru could be trained through the implementation of project based learning strategies in The Equation of Progressive Wave and Stationary Wave subject. Key Words: project based learning, communication, communication skills, The Equation of Progressive Wave and Stationary Wave